2000
DOI: 10.1111/j.1749-6632.2000.tb06712.x
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Vaccines: Antiidiotypic Antibody, Recombinant Protein, and Viral Vector

Abstract: The colorectal cancer antigen GA733 (also termed CO17‐1A, KSI‐4, Ep‐CAM, KSA) has proved to be a useful target in passive immunotherapy with monoclonal antibody and in active immunotherapy with antiidiotypic antibodies in cancer patients. The GA733 antigen was molecularly cloned and expressed in baculovirus (BV), adenovirus (AV), and vaccinia virus (VV). Recombinant BV‐, VV‐, and AV‐GA733 induced antigen‐specific cytotoxic antibodies and proliferative and delayed‐type hypersensitive lymphocytes. However, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Passive immunization with CO17-1A (Panorex) induced survival benefit compared with untreated patients in the clinical setting of minimal residual disease (16,17). Active immunization has been conducted using anti-Id vaccines (18 -20), recombinant protein (13,21), and viral vectors (22), but has shown limited clinical efficacy so far.…”
mentioning
confidence: 99%
“…Passive immunization with CO17-1A (Panorex) induced survival benefit compared with untreated patients in the clinical setting of minimal residual disease (16,17). Active immunization has been conducted using anti-Id vaccines (18 -20), recombinant protein (13,21), and viral vectors (22), but has shown limited clinical efficacy so far.…”
mentioning
confidence: 99%
“…The recent licensure of DC-based vaccine Provenge ® for the treatment of prostate cancer in humans along with the approval of Oncept™ as therapy for oral melanoma in dogs lends support to the clinical promise of cancer vaccines (Aurisicchio and Ciliberto 2011). Many studies have shown that Ad-based vaccines are more efficient in generating antitumor immunity than vaccines based on other delivery systems (Basak et al 2000;Okur et al 2011). Ad vectors emerged as promising gene therapy vectors and recombinant vaccine carriers owing to their well-characterized molecular genetics, high yield propagation capacity amenable to pharmaceutical scale production, and biological characteristics (Choi and Yun 2013).…”
Section: Adenovirus-based Cancer Vaccinesmentioning
confidence: 99%
“…The low frequency of immune responders to Ep-CAM in rhesus monkeys prompted us to go back and re-examine the vaccine capability to break tolerance to self in smaller animal models in mice, where a variety of strains with well-defined MHC haplotypes are available and where it is possible to work with larger numbers of individuals [14].…”
Section: Mep-cam Vaccination Breaks Inmmunological Tolerance Only In mentioning
confidence: 99%
“…To date, however, only one report has described tumor protection induced by the self mouse Ep-CAM (mEp-CAM) vaccination in the presence of a high dose of IL-2 [14].…”
Section: Introductionmentioning
confidence: 99%